THE IMPROVEMENT OF THE SYSTEM OF VETERINARY RADIOLOGICAL MONITORING OF RADIOACTIVE CONTAMINATION OF RAW MATERIALS OF ANIMAL AND VEGETABLE ORIGIN IN UKRAINE - Прокопенко, Т. О. (Scientific Progress & Innovations, 2013)
An integral component of radiation safety in the 25th year of overcoming the consequences of the Chernobyl disaster is the control of radionuclides in agricultural raw materials and feed. The basis of radiation safety is radiological supervision and monitoring of radioactive contamination of raw materials of animal and plant origin and prevention of radionuclides in the human body and animals. Implementation of veterinary radiological monitoring will ensure efficient use of existing organizational structures and means for observation of objects of veterinary supervision.